Turning on/off satellite droplet ejection for flexible sample delivery on digital microfluidics. Issue 20 (25th September 2020) - Li, Haoran; Shen, Ren; Dong, Cheng; Chen, Tianlan; Jia, Yanwei; Mak, Pui-In; Martins, Rui P.
Abstract : Convenient electric control and electrode design allow flexible sample delivery on-chip in a wide range on microfluidics. Abstract : Digital microfluidics has the potential to minimize and automate reactions in biochemical labs. However, the complexity of drop manipulation and sample preparation on-chip has limited its incorporation into daily workflow. In this paper, we report a novel method for flexible sample delivery on digital microfluidics in a wide volume range spanning four orders of magnitude from picoliters to nanoliters. The method is based on the phenomenon of satellite droplet ejection, triggered by a sudden change in the strength of the electric field across a drop on a hydrophobic dielectric surface. By precisely modulating the actuation signal with convenient external electric controls, satellite droplet ejection can be turned on to dispense samples or turned off to transport picking-up drops. A pico-dosing design is presented and validated in this work to demonstrate the direct and flexible on-chip sample delivery. This approach could pave the way for the acceptance of microfluidics as a common platform for daily reactions to realize lab-on-a-chip.